BIOMASS PRODUCTION AND NODULATION OF GREEN MANURE LEGUMES IN COCONUT BASINS IN LATERITE SOIL AND THEIR INFLUENCE ON SOIL FERTILITY - G.V. Thomas; M.V. Shantaram (International Coconut Community Journal, 1993)
Biomass production, nitrogen yield and nodulation by ten species of green manure legumes were compared in coconut basins in a root (wilt) affected garden under laterite soil type. Pueraria phaseoloides, Calopogonium mucunoides and Mimosa invisa were superior to others and yielded 28.45, 27.21 and 24.97 kg of biomass and 196.2, 186.5 and 187.6 g of nitrogen basin-1, respectively. The performance of Mucuna bracteata Crotalaria juncea and Macroptilium atropurpureum were also better with a biomass production of 16‑21 Kg basin-1 and nitrogen yield of 108‑140 g basin-1. Incorporation of green manures obtained from C. mucunoides, P. phaseoloides and M. invisa resulted in an increase in the level of major nutrients viz. N, P and K in coconut basin soils. Mineralisation of carbon was also greater in green manured coconut basin soils when compared to that in control. The increase in nutrient levels and mineralisation of carbon was more in treated basins at 30 days of incorporation of green manures when compared to the levels before the harvest of the legumes and at 60 days of incorporation.